Effects of carbohydrate and caffeine mouth rinsing on strength, muscular endurance and cognitive performance - Raci Karayigit; Ajmol Ali; Sajjad Rezaei; Gulfem Ersoz; Angel Lago-Rodriguez; Raúl Domínguez; Alireza Naderi (Taylor & Francis Group, 2021)
Background Carbohydrate (CHO) and caffeine (CAF) mouth rinsing have been shown to enhance endurance and sprint performance. However, the effects of CHO and CAF mouth rinsing on muscular and cognitive performance in comparison between male and female athletes are less well-established. The aim of this study was to examine the effect of CHO and CAF rinsing on squat and bench press 1 repetition maximum (1-RM) strength, 3 sets of 40% of 1-RM muscular endurance and cognitive performance in both male and female athletes. Methods Thirteen male and fourteen female resistance-trained participants completed four testing sessions following the rinsing of 25 ml of i) 6% of CHO (1.5 g); ii) 2% CAF (500 mg), iii) combined CHO and CAF (CHOCAF) solutions or iv) water (PLA) for 10 s. Heart rate (HR), felt arousal (FA), ratings of perceived exertion (RPE) and glucose (GLU) were recorded throughout the test protocol. Results There were no significant differences in squat and bench press 1-RM, HR, RPE and GLU (p > 0.05) for males and females, respectively. FA was significantly increased with CAF (p = 0.04, p = 0.01) and CHOCAF (p = 0.03, p = 0.01) condition in both males and females, respectively. Squat endurance performance in the first set was significantly increased with CHOCAF condition compared to PLA in both males (p = 0.01) and females (p = 0.02). Bench press endurance was similar for all conditions in both genders (p > 0.05). Cognitive performance was significantly increased with CHOCAF compared to PLA in males (p = 0.03) and females (p = 0.02). Conclusion Combined CHO and CAF mouth rinsing significantly improved lower body muscular endurance and cognitive performance in both males and females.